Aplikasi Berbagai Dosis dan Dua Jenis Guano pada Budidaya Tanaman Jagung Pakan (Zea mays. L) di Lahan Podsolik - M. Azai; Nur Hafizah; Mahdiannoor (Rawa Sains: Jurnal Sains STIPER Amuntai, 2018)
Corn feed is one animal feed that has many advantages, as corn feed is used for metabolic energy sources. Podsolic land is a land with very low nutrient value. This study aims to (i) determine the effect of various doses, and two types of guano interactions, (ii) determine the effect of various doses of guano, (iii) find out influence of two types of guano, (iv) get the best interaction, (v) get the best dose, (vi) get the best type of guano in the cultivation of corn feed in podsolic land. This research was conducted in Hawang Village, Limpasu District, Hulu Sungai Tengah Regency, from March to June 2018. They are using Group Random Design (GRD) Factorial 2 factors. The first factor is various doses of guano with five levels: d1 = 1.5 kg. plot-1, d2 = 3 kg. plot-1, d3 = 4.5 kg. plot-1, d4 = 6 kg. plot-1, d5 = 7.5 kg. plot-1. The second factor is two types of guano with two levels: g1 = bat guano, g2 = swallow guano. The results showed that the interaction between various doses and two types of guano had no effect on growth and yield, except that the effect was very significant on long cob weighted, whereas a single factor of various doses had significant and very real effect on all observation variables and the factor of two types of guano had no effect on all variables. Except for significant effect on plant height growth at the age of 56 HST.